(untitled) (Manila, Philippines, 2009)
Contents: Tourism sector in Cambodia; Alternative tourism scenarios; Baseline environmental condition; Strategic environmental assessment of tourism impacts...
Keywords: Tourism,Du lịch; Cambodia,Campuchia